Avaliação da deformação miocárdica em repouso e durante o exercício em pacientes hipertensos sem hipertrofia do ventrículo esquerdo - Almeida, Rômulo Leal (2021)
Introduction: systemic arterial hypertension has a high prevalence and low control rates, being responsible for functional and structural changes in several organs, including the heart. Speckle tracking echocardiography allows the analysis of the dynamics of ventricular contraction, enabling the early detection of myocardial dysfunction. Objectives: to evaluate the degree of myocardial deformation at rest and at peak aerobic exercise in hypertensive patients without left ventricular hypertrophy (LVH) and compare these parameters with healthy controls. Methods: this is an observational cross-sectional study, carried out from October 2020 to May 2021, in patients diagnosed with arterial hypertension, with preserved ejection fraction, without LVH and of both genders. Healthy individuals with characteristics similar to hypertensive individuals were included in the study. Volunteers underwent myocardial deformity assessment by measuring global longitudinal strain (GLS), at rest and at peak stress with speckle tracking during a maximum effort test. Normality and homoscedasticity were assessed using the Shapiro-Wilk and Levene tests, respectively. Mann Whitney t or U tests, one-way ANOVA and Spearman's correlation test were used and the accepted significance level was p < 0.05. Cohen's d was used to assess the size of the effect reported on the variation in myocardial strain between groups. Results: twenty volunteers were evaluated, matched for sex, age, body mass index and echocardiographic parameters. The hypertensive group had higher SBP (137.3 ± 10.5 mmHg vs 122.3 ± 9.3 mmHg, p = 0.01) and MAP (104.0 ± 9.2 mmHg vs 94.1 ± 5, 4 mmHg, p = 0.03) compared to the control group. The other characteristics and hemodynamic parameters at rest and at the exercise test were similar between groups (p>0.05 for all comparisons). In the analysis of the GLS, there were no significant differences in hypertensive individuals in relation to the control, either in the baseline GLS (18.5 ± 1.9 vs 18.0 ± 1.6%, respectively; p = 0.48) or during the Peak GLS (21.0 ± 1.4 vs 22.0 ± 2.8%, respectively; p = 0.39). In the intragroup analysis between baseline vs peak GLS, there is a statistical difference in the hypertensive group (18.5 ± 1.9 vs 21.0 ± 1.4%, p=0.003) and in the control group (18.0 ± 1.6 vs 22.0 ± 2.8%, p=0.001). Conclusion: hypertensive patients with controlled blood pressure, without cardiac remodeling and preserved ejection fraction present similar GLS compared to control volunteers. However, hypertensive individuals have less clinical variation from left ventricular systolic contractility to physical stress.